IPTEKS PENERAPAN METODE PENENTUAN HARGA JUAL NORMAL DALAM PENENTUAN HARGA JUAL JASA (STUDI KASUS PADA USAHA PHOTOCOPY GLORIA MANADO) - Pontoh, Winston; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2018)
The role of information technology and competition for the recent era is main trigger for rapid growth of business. In order to win the competition, most of business unit especially for the small medium enterprise their selling price (product or service) as it is the main key to estimate the target profit. The business of photocopy is the simple business with rapid turn over but require high investments. This business have growing fast in Manado City, North Sulawesi. The main problem of this business for Manado City is lower skill of managerial for each owners. Based on method to estimate selling price on photocopy business then return on investment provide better information to establish the service selling price.